The significance of hypoechoic lesion directed and transition zone biopsies in improving the diagnostic ability in prostate cancer - (:unkn) unknown (My University, 2001)
Contemporarily, systematic peripheral zone (PZ) biopsies under transrectal ultrasonography (TRUS) guidance are the standard procedure in the diagnosis of prostate cancer. Although, it is widely accepted that the most common appearance of cancer tissue is hypoechoic nodule in the PZ, the diagnostic yield of additional lesion directed biopsies is the subject of debate. Similarly, the place of routine application of transitional zone (TZ) biopsies is not clear. In this study, the diagnostic contribution of lesion directed and TZ biopsies into systematic PZ biopsies were assessed. A total of 271 patients were admitted to the outpatient department with lower urinary tract symptoms underwent TRUS guided prostate biopsies owing to elevated prostate specific antigen (PSA > 4 ng/ml) and/or abnormal digital rectal examination findings. All biopsies were performed with a systematic approach (3 specimens taken from the base, midgland, apex of the right and left sides of PZ) and hypoechoic lesion directed biopsies plus systematic random TZ biopsies (one core taken from each side). Prostate cancer was detected in 89 patients (32.8%) undergoing biopsy. The sonographic appearance of hypoechoic PZ lesions was observed in 120 patients. Of the patients with carcinoma, 66.3% (59/89) had hypoechoic PZ lesions. Among the patients hypoechoic PZ lesions on TRUS 49.2% (59/120) revealed carcinoma on biopsy, whereas 33.7% of patients (30/89) harboring cancer demonstrated no sonographic abnormalities. In contrast, among the 55.7% of men (151/271), who had no hypoechoic PZ lesions on TRUS, 20% had cancer. Only 3 patients had their cancer found uniquely in the biopsy sample taken from the hypoechoic PZ lesion with negative systematic PZ biopsies. Consequently, 3.4% of cancer cases would have been missed in the absence of the lesion directed biopsies. On the other hand, the cancer detection rate on systematic biopsy within the TZ was 1.5%; in all of these cases systematic biopsies from PZ also positive. As a conclusion, although the detection rate of lesion directed biopsies was low, since insertion of an additional needle bears very little infliction for the patient, it is justified to perform lesion directed biopsies. On the other hand, TZ biopsies had no significant yield in cancer detection in patients undergoing initial systematic TRUS guided biopsy.
Keywords: Biopsy; Diagnosis; Prostatic neoplasms; Ultrasonography